2018
DOI: 10.1103/physreva.97.033617
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transitions, pseudogap behavior, and BCS-BEC crossover in Fermi-Fermi mixtures

Abstract: We study the mass imbalanced Fermi-Fermi mixture within the framework of a two-dimensional lattice fermion model. Based on the thermodynamic and species dependent quasiparticle behavior we map out the finite temperature phase diagram of this system and show that unlike the balanced Fermi superfluid there are now two different pseudogap regimes as PG-I and PG-II. While within the PG-I regime both the fermionic species are pseudogapped, PG-II corresponds to the regime where pseudogap feature survives only in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 99 publications
(131 reference statements)
0
10
0
Order By: Relevance
“…At η = 1 corresponding to zero imbalance in mass, both the pseudogap scales collapses to one. The phase diagram shows that, while akin to the population imbalanced system the T c is strongly suppressed by imbalance in mass, the short range pair correlations survive over a large temperature regime of T ∼ 2T c [124].…”
Section: Mass Imbalanced S-wave Superfluidsmentioning
confidence: 97%
See 3 more Smart Citations
“…At η = 1 corresponding to zero imbalance in mass, both the pseudogap scales collapses to one. The phase diagram shows that, while akin to the population imbalanced system the T c is strongly suppressed by imbalance in mass, the short range pair correlations survive over a large temperature regime of T ∼ 2T c [124].…”
Section: Mass Imbalanced S-wave Superfluidsmentioning
confidence: 97%
“…Evidently, all the numerical approaches have different set of merits and caveats, and consequently different regimes of applicability. We now discuss the numerical implementation of the SPA technique in some detail [122,123,124,125,126]. The merits of this technique rests on its applicability, in principle to systems of arbitrary dimensions and lattice sizes, with moderate computation cost and its access to real frequency properties of the system.…”
Section: Static Path Approximation (Spa)mentioning
confidence: 99%
See 2 more Smart Citations
“…[5,10,16] Most investigation of ultracold Fermi gas with SOC focus on the mass-balanced cases. [17][18][19][20][21][22][23][24][25][26][27][28] Differently, the twospecies (mass-imbalanced) Fermi-Fermi degenerate mixture would show more special properties, [29][30][31][32][33][34][35][36][37][38][39][40] It is found that Feshbach resonance can occur in the 6 Li- 40 K mixture, [29] and this result plays an indispensable role in exploring the multibody physics of strongly interacting regions and opens up a way for people to study mixed Fermi materials. Recently, the mixture of 161 Dy- 40 K offers an ideal platform with mass imbalance and strong interaction, [32] and it can effectively inhibit the elastic loss near the resonance.…”
Section: Introductionmentioning
confidence: 99%